PENGEMBANGAN MEDIA POWTOON DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA DI MI ASWAJA I MOJO KEDIRI - Nuriana Azka; Lusiana; Prasetya Rachmawan; M. Rosyid Sobikhi; Nurul Widayanti (Insititut Agama Islam Agus Salim Metro Lampung, 2023)
The world is currently being tested with health problems, namely the COVID-19 pandemic which has greatly affected the world of education and aspects of life. So learning must be done online or online. Online learning is an alternative that can overcome these problems. Learning media that can be used in online learning is Powtoon learning media which can make students not bored in learning because this web application has many interesting features. The purpose of this study was to determine the use of the Powtoon application which can be a learning media solution during the Covid-19 pandemic. The method used in this research is development (RnD). The results of the validation of the material indicate a valid category by obtaining a value of 3.51. The media aspect got a score of 3.45 with a valid category, the display aspect of the program got a score of 3.25 d in the valid category, the technical quality and program effectiveness aspects got a score of 3.5 with a valid category.